Gallic, ellagic acids and their oral combined administration induce kidney, lung, and heart injury after acute exposure in Wistar rats. (December 2022) - Hurtado-Nuñez, Grecia-Elena; Cortés-Rojo, Christian; Sánchez-Ceja, Sandra-Guadalupe; Martínez-Flores, Héctor-Eduardo; Salgado-Garciglia, Rafael; Bartolomé-Camacho, María-Carmen; García-Pérez, Martha-Estrella
Abstract: Gallic (GA) and ellagic (EA) acids are present in foods, medicinal plants, teas, and dietary supplements. An acute toxicological study was conducted by oral administration of both compounds alone (200, 1000, and 2000 mg/kg) and combined (2000 mg/kg) and their effects on the electron transport chain (ETC) and the ROS production in kidney mitochondria further evaluated. All treatments induced a dose-dependent heart, lung, and kidney injury. However, the intensity of these effects varied according to the substance, with greater cardiac and renal toxicity for EA and pulmonary injury for GA, while the combination attenuated the toxicity of the isolated molecules. All substances inhibited the activity of complexes II, III, and IV of the ETC from renal mitochondria. However, no changes were observed regarding mitochondrial ROS production. These compounds have a non-negligible inherent deleterious potential, so their uncontrolled use at high doses (≥200 mg/kg) could cause undesirable effects. Highlights: Gallic and ellagic acids dietary supplements sale has increased in recent years. Gallic, ellagic acids and their combination induce kidney, lung, and heart damage. Renal mitochondrial electron chain complexes were impaired for these substances. Kidney injury was not related to induction of mitochondrial ROS production. Uncontrolled use of these substances may provoke adverse events.